2006
DOI: 10.1021/ac060436i
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Analysis of Pharmaceutical Compounds by MALDI-TOF Mass Spectrometry

Abstract: In this report, we discuss key issues for the successful application of MALDI-TOF mass spectrometry to quantify drugs. These include choice and preparation of matrix, nature of cationization agent, automation, and data analysis procedures. The high molecular weight matrix meso-tetrakis(pentafluorophenyl)porphyrin eliminates chemical noise in the low-mass range, a "brushing" spotting technique in combination with prestructured target plates enables fast preparation of homogeneous matrix crystals, and addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 21 publications
2
70
0
Order By: Relevance
“…Dwell time of the ions does not contribute significantly to the analysis time, although the detection time of ions can take second(s) per scan in Fourier-transform ion cyclotron resonance (FTICR) MS and Orbitrap MS. With a high repetition rate laser that fires at 1,000-2,000 Hz, an averaged mass spectrum of high quality can be obtained in a few seconds with MALDI-time-of-flight (TOF) MS or MALDI-triple quadrupole MS (Hatsis et al, 2003;McLean, Russell, & Russell, 2003;Moskovets et al, 2006;Rathore et al, 2008). For quantitative analysis of, for instance, HIV protease inhibitors, analysis times for a single spot on the target plate have been reported of $3 min for MALDI-FTICR MS (20 Hz laser), $30 sec for MALDI-TOF MS (50 Hz laser), and $5 sec for MALDI-triple quadrupole MS (1,000 Hz laser; van Kampen et al, 2006Kampen et al, , 2008aKampen et al, ,b, 2009b. Recently, an analysis time of 1.75 min for an entire 384-well target plate was reported for an assay to screen for small-molecule inhibitors of enzymes with MALDI-triple quadrupole MS (Rathore et al, 2008).…”
Section: A High-throughput Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Dwell time of the ions does not contribute significantly to the analysis time, although the detection time of ions can take second(s) per scan in Fourier-transform ion cyclotron resonance (FTICR) MS and Orbitrap MS. With a high repetition rate laser that fires at 1,000-2,000 Hz, an averaged mass spectrum of high quality can be obtained in a few seconds with MALDI-time-of-flight (TOF) MS or MALDI-triple quadrupole MS (Hatsis et al, 2003;McLean, Russell, & Russell, 2003;Moskovets et al, 2006;Rathore et al, 2008). For quantitative analysis of, for instance, HIV protease inhibitors, analysis times for a single spot on the target plate have been reported of $3 min for MALDI-FTICR MS (20 Hz laser), $30 sec for MALDI-TOF MS (50 Hz laser), and $5 sec for MALDI-triple quadrupole MS (1,000 Hz laser; van Kampen et al, 2006Kampen et al, , 2008aKampen et al, ,b, 2009b. Recently, an analysis time of 1.75 min for an entire 384-well target plate was reported for an assay to screen for small-molecule inhibitors of enzymes with MALDI-triple quadrupole MS (Rathore et al, 2008).…”
Section: A High-throughput Analysismentioning
confidence: 99%
“…Srinivasan et al (1999) reported that some porphyrins could act as auto-matrices, and various porphyrins have been tested as matrix in MALDI-MS (Jones, Lamb, & Lim, 1995;Chen & Ling, 2002). In particular, meso-tetrakis(pentafluorophenyl)porphyrin (F20TPP; MW 974) appears to be a useful matrix for the analysis of small molecules with MALDI-TOF MS (Ayorinde et al, 1999;Ayorinde, Garvin, & Saeed, 2000;Hlongwane et al, 2001;Ayorinde, Bezabeh, & Delves, 2003;van Kampen et al, 2006van Kampen et al, , 2007Yu et al, 2006;Kosanam et al, 2007). Ayorinde et al (1999) compared the use of a-cyano-hydroxycinnamic acid (CHCA) and F20TPP for the analysis of alkylphenol ethoxylates and found that F20TPP generated spectra with significantly less matrix interference in the low mass range (see Fig.…”
Section: B High Molecular Weight Matricesmentioning
confidence: 99%
See 1 more Smart Citation
“…van Kampen and colleagues [33] examined such issues as the matrix (i.e. nature and preparation), the inclusion of Li þ to facilitate formation of cationized drug species, automation and data analysis procedures.…”
Section: Low Molecular Mass Analytesmentioning
confidence: 99%
“…plasma, serum, urine and cerebrospinal fluid). [10] Since the introduction of a mass spectrometry platform which consists of MALDI source with a high repletion solid-state UV laser (1 kHz, 349 nm) in combination with a triple quadrupole mass spectrometer (MALDI-QqQ-MS) few articles have been reported demonstrating that this new technology can be applied for high accurate and precise determinations of concentrations of small molecules [11] with CVs <15/20%, according to the most recent FDA guidelines. [12] Therefore, we decided to use this new technology and to study its feasibility for high-throughput and ultrafast measurement of plasma concentrations of the antiretroviral drug TNV in plasma from HIV adults using an isotope dilution method.…”
Section: Introductionmentioning
confidence: 99%